Transition to a novel advanced integrated vitrectomy platform: comparison of the surgical impact of moving from the Accurus vitrectomy platform to the Constellation Vision System for microincisional vitrectomy surgery - Murray TG (Dove Medical Press, 2013)
Timothy G Murray,1,2 Andrew J Layton,3 Kuo B Tong,3 Michael Gittelman,2 Azeema Latiff,1,2 Daniel Gologorsky,2 Michael M Vigoda21Murray Ocular Oncology and Retina, Miami, FL, USA; 2Bascom Palmer Eye Institute, Anne Bates Leach Eye Hospital, Departments of Ophthalmology, Anesthesiology and Radiation Oncology, University of Miami Miller School of Medicine, Miami, FL, USA; 3Quorum Consulting, San Francisco, CA, USABackground: Microincisional vitrectomy surgery (MIVS) is the current standard surgical approach for pars plana vitrectomy. Historically, the most common surgical platform for vitrectomy surgery, since its introduction in 1997, has been the Accurus vitrectomy system. Recent introduction of the next generation of vitrectomy platforms has generated concerns associated with transitioning to new technology in the operating room environment. This study compared, in a matched fashion, surgical use of the Accurus vitrectomy system and the next generation Constellation Vision System to evaluate surgical efficiencies, complications, and user perceptions of this transition.Methods: Electronic health records were abstracted as a hospital quality assurance activity and included all vitreoretinal surgical procedures at the Bascom Palmer Eye Institute, Anne Bates Leach Eye Hospital, during two discrete 12-month time periods. These two periods reflected dedicated usage of the Accurus (June 2008–May 2009) and Constellation Vision (July 2009–June 2010) systems. Data were limited to a single surgeon and evaluated for operating room (OR) total time usage/day, OR case time/case, and OR surgical time/case. Further analysis evaluated all patients undergoing combined MIVS and clear cornea phacoemulsification/intraocular lens (IOL) implantation during each individual time period to determine the impact of the instrumentation on these parameters. All records were evaluated for intraoperative complications.Results: Five hundred and fourteen eligible patients underwent MIVS during the 2-year study windows, with 281 patients undergoing surgery with the Accurus system and 233 patients undergoing surgery with the Constellation system. Combined MIVS and phacoemulsification with IOL implantation was performed 141 times during this period with the Accurus and 158 times during the second study period with the Constellation. Total number of patients operated per day increased from 7.55 with Accurus to 8.53 with Constellation. Surgical room time decreased from 56 minutes with Accurus to 52 minutes with Constellation, and procedure time decreased from 35 minutes with Accurus to 31 minutes with Constellation (P < 0.004). Combined MIVS/phacoemulsification surgery saw similar declines in surgical room time and procedure time (P < 0.001). Subset analysis of procedures limited by case number per day (eg, four cases/day, five cases/day, six cases/day, and seven or more cases/day) showed similar outcomes with a decrease in surgical room time and procedure time. No increases in surgery-related complications were noted by quality assurance review during these time periods.Discussion: Transitioning to advanced surgical technology is a complex issue for the surgeon, the hospital team, and the hospital administration. This study documents improvement in three significant measures of surgical efficiency: operative number of patients per day, operative room time, and surgical procedure time that reflect the positive impact of the novel, combined, integrated, posterior and anterior, ophthalmologic surgical platform of the Constellation Vision System. These data are imperative to evaluate the impact of transition from one surgical platform to another. During this transition, hospital quality assurance review and surgeon evaluation of operative complications showed no increased concerns for the shift from the Accurus to the Constellation Vision System surgical platform. Further, both operative staff and surgeons felt that the transition to the Constellation was not associated with increases in difficulty with setup, turnover, or use and that the Constellation decreased safety concerns for surgical usage. Ultimately, in this case, new technology benefited the surgeon, the patient, and the hospital.Keywords: MIVS, vitrectomy, new technology